(untitled) (CAHIERS MAGELLANES-NS, 2024)
Abstract:The gall of this study is to assess the effects of long term exposure to lead acetate on histological architecture of liver in white rat. 24 animals were used in the experiment, which distributed to 4 groups, 1st group (G1) control group was injected intraperitonially by distilled water 1 ml/kg body weight for three month. 2nd group (G2) was injected intraperitonially by lead acetate 12 mg / kg body weight / 10 days for three month. 3rd (G3) was injected intraperitonially by lead acetate 12 mg / kg body weight / 10 days for three months and then injected intraperitonially by 0.2 ml Atropine sulfate for 5 days. 4th (G4) was injected intraperitonially by lead acetate 12 mg / kg body weight / 10 days for three months and then injected intraperitonially by 0.2 ml Atropine sulfate for 7 days. The histological results of G2 showed liver cells with vacuolar degeneration, pyknosis of a number of cell nuclei, and the disappearance of nuclei from other necrotic liver cells. Blood sinusoids were containing dark-colored kupffer cells., results of group G3 and G4, treated with lead acetate for three months and treated for 5 and 7 days respectively with the drug atropine sulfate, showed The presence of normal-shaped hepatic cells interconnected with other cells, including blood sinusoids containing kupffer cells. The central vein in the hepatic lobule showed decomposed blood with some white blood cells in its lumen. The central vein extended with blood sinusoids filled with enlarged kupffer cells. The hepatic cells were found in folded rows and appeared polygonal, and each cell had two nuclei. Physiological results showed of lactate dehydrogenase (LDH) and acid phosphatase (ACP) of all groups, as it was observed that there was a significant increase in the concentration of them at a significant level in G2 compared to the G1. While the results showed a significant lowering in their concentration in both G3 and G4 . Conclusion: The results of this study revealed the occurrence of histological and physiological changes in the liver as a result of exposure to lead, and that the drug atropine sulfate played a positive role in the healing process.Key words: Cerebellum, lead acetate, histological changes